CHILDFREE ACCORDING TO THE VIEW OF THE COMMUNITY OF MEDAN DISTRICT JOHOR MEDAN CITY - ABU BAKAR (Universitas Dharmawangsa, 2023)
Some married couples decide to limit their offspring with clear reasons and are justified by the Shari'a, while others consider that having many children is a blessing for which one should be grateful. All of that is because everyone must have different perspectives, reasons and also different experiences in living a household life. Unlike the case with a handful of married couples who think that happiness in the household is not only obtained from the birth of a child. And marriage does not have to have children or offspring. In Indonesia, for example, we know the name Veronica Wilson, who decided not to have children. Likewise with Victoria Tunggono who decided to live a family life without having children who are popularly known as